NUSYUZ IN AL-QUR’AN - Tarmizi, Tarmizi (Journal of Islam and Science, 2019)
In the Qur’an, there are commands, prohibitions, warnings, instructions and stories of previous Prophets. Study of the content of al-Qur'an is not only a worship of Allah but also to get guidance that lives in accordance with Islamic law. Al-Qur'an thematic study is one of the methods of studying the Qur'an that is practiced by Muslim scholars and ulama. One of the thematic studies contained in al-Qur'an is the association of husband and wife like nusyuz. Nusyuz is a violation of a shared commitment to what is obligatory in the household. The study of nusyuz needs to be done in relation to understanding, asbabun nuzul, ulama's review as well as a review of Islamic law on these actions. By conducting a study of the nusyuz, we are expected to be able to better understand the related matter, giving knowledge to others in order to avoid the actions that lead to the nusyuz.